CRIMINAL LIABILITY OF FISHERY PERPETRATOR ACCORDING TO FISHERY LAW NUMBER 45 OF 2009 CONCERNING AMENDMENT TO LAW NUMBER 31 OF 2004 - Yulia Monita; Nys. Arfa; Zulham Adamy (Berumpun: International Journal of Social, Politics, and Humanities, 2020)
Many occurrences of fisheries criminal offenses make the writer interested to learn about criminal provisions and the responsibility of the perpetrators according to Law No. 45 of 2009 concerning amendments to Law No. 31 of 2004 concerning Fishery. By studying, understanding, and analyzing these articles of law, the author significantly obtains the picture of whether this Fishery Law is appropriate and able to force the perpetrator of their responsibility for their actions. The purposes of this paper are 1) To analyze the patterns of fishery criminal so the perpetrators could be charged their responsibilities according to Law No. 45 of 2009, 2) To study and analyze how to determine the penalties according to the Law No. 45 of 2009. This paper is a qualitative descriptive. The method of this research is normative law with conceptual and institutional approaches. The result of the study showed that legislation in Indonesia relating to Fisheries, administratively, there are still several articles that are sticking out and controversy according to Law No. 45 of 2009 concerning amendments to Law No. 31 of 2004 concerning Fishery. For small fishermen who do not have a Yachting Approval Letter (SPB) in Indonesia should be subjected to administrative sanctions such as paying compensation. If administrative sanctions are not implemented, then the principle of ultimum remedium can be applied as a last choice in violations of fisheries and there are still several articles that are detrimental to the interests of the State as well as the interests of local fishermen which, if seen from criminal liability, may be imposed.